A8 DIETARY TRYPTOPHAN MODULATES KYNURENINE AND INDOLE PRODUCTION IN HEALTHY INDIVIDUALS. (4th March 2021) - Rueda, G H; Causada-Calo, N; Borojevic, R; Nardelli, A; Constante, M; Loonen, L; Wells, J; Sokol, H; Verdu, E; Bercik, P
Abstract: Background: Tryptophan is an essential amino acid that is transformed by host and gut microbial enzymes into multiple bioactive metabolites that regulate immunity, mood and circadian rhythms. In particular, indoles, produced by gut bacterial metabolism of tryptophan, have recently gained central attention. Indoles are activators of the aryl hydrocarbon receptor (AhR), which is crucial for the maintenance of intestinal homeostasis and immunity. Tryptophan supplementation in fortified foods have been advocated to prevent chronic inflammatory conditions, from autism to chronic inflammation. However, whether dietary tryptophan supplementation affects immune function, tryptophan metabolic pathways and gastrointestinal symptoms in healthy subjects, is unknown. Aims: To assess whether tryptophan supplementation, in healthy subjects on a low tryptophan diet, induces changes in microbiota-derived metabolites (indoles), host cytokine production or gut symptoms. Methods: We performed a randomized, double blind, placebo-controlled, crossover study in 20 healthy individuals, between 18 and 75 years old, following a regular diet. Subjects were instructed to start a standardized low tryptophan diet and were randomly assigned to a 3-week tryptophan supplement (3gr/day) or placebo. After a 2-week washout period, subjects were crossed over to the opposite 3-week intervention arm. Self-administered questionnaires (GSRS, DASS21 and HADS) were used to assess gastrointestinal symptoms and mood/anxiety/stress. Stool, urine and blood samples were collected to measure tryptophan metabolites (kynurenine pathway and indoles) and cytokines. Results: Supplementation of tryptophan was well tolerated and no changes in gastrointestinal symptoms or mood/anxiety were found. Compared with placebo, tryptophan supplementation increased urinary and plasma levels of indoleamine 2, 3-dioxygenase (p= 0.002 and p= 0.02, respectively), a key enzyme in the kynurenine pathway, and of several indoles (p= 0.0008 and p= 0.01, respectively), suggestive of activation of microbial and host metabolic pathways. However, there were no measurable changes in the host cytokine production. There was a positive correlation between fecal kynurenine levels and anxiety and depression scores, suggesting that microbial metabolites may impact host behavior in humans. Conclusions: Dietary tryptophan supplementation in healthy individuals was safe and had a measurable effect on microbial and host metabolism, mainly kynurenine and indole pathways, with known immunomodulatory properties. Although no effects on cytokine production were found, further studies are warranted to investigate tryptophan supplementation in disorders with altered AhR pathway, such as inflammatory bowel disease, metabolic syndrome and celiac disease. Funding Agencies: None